Lingkungan Toko Terhadap Kepuasan Konsumen dalam Berbelanja - Kurniawan, Brahma Wahyu (STIE Malangkucecwara, 2018)
The results of this study are as follows: (1) location of the store has a significant influence on consumer satisfaction in shopping, with a value of β = 0.590; (2) The layout of the store has a significant influence on consumer satisfaction in shopping, with a value of β = 0.241; (3) The atmosphere shop has a significant influence on consumer satisfaction in shopping, with a value of β = 0.343; (4) Simultaneously, store environment variables consisting of store location, store layout and atmosphere of the store has a significant impact on consumer satisfaction in shopping, with a value of F = 86.482 and the value of Adjusted R Square of 0.721. Of these three variables, the location of the store is the dominant variable that affects customer satisfaction in shopping.